The Legitimacy of Human Rights “Found in the Street": An Analysis in The Light of Paulo Freire’s Liberating Ethics (Revista Iberoamericana de Bioética, 2024)
This article proposes an analysis of the connection between human rights “found in the street", and the ethics advocated by the Brazilian pedagogue Paulo Freire, whose work is imbued with the quest for freedom for the "socially oppressed". The study involves a narrative review of the literature in order to examine possible links between Freire's "universal ethics of the human being" and the approach of “liberating human rights”, with social transformation at the core of its legal practices, and which seeks to overcome the inequality, hunger and poverty that undermine the life opportunities of thousands of Brazilians. Freire's vision of ethics provides legal practitioners and Brazilian society as a whole with tools to reflect on social injustice and build an egalitarian world with freedom and dignity for all.
Keywords: human rights; pedagogy; ethics; social injustice; freedom